Evaluation of the fusion partner cell line SPYMEG for obtaining human monoclonal antibodies against influenza B virus - SONI, Priyanka; YASUHARA, Atsuhiro; TAKENAGA, Toru; IWATSUKI-HORIMOTO, Kiyoko; URAKI, Ryuta; ITO, Mutsumi; SASAKI, Tadahiro; IKUTA, Kazuyoshi; YAMAYOSHI, Seiya; KAWAOKA, Yoshihiro (Journal of Veterinary Medical Science, 2018)
Influenza B virus has been known to infect humans and other animals, including seals. Vaccination efficacy varies across seasons. Human monoclonal antibodies (mAbs) can be useful for developing novel vaccines, guided by epitope analysis, and can be used therapeutically. Hybridoma technology has been used to make mAbs. Here we evaluated SPYMEG as a fusion partner cell line for human mAb generation specific to influenza B hemagglutinin (HA). SPYMEG is a human/murine myeloma partner cell line that has previously been used to generate human mAbs that recognize the HA of influenza A and B viruses. Peripheral blood mononuclear cells were obtained from 16 volunteers, previously vaccinated with the 2014–2015 trivalent seasonal influenza vaccine, and were fused with SPYMEG to yield hybridomas. The resulting hybridomas were screened for antigen-specific antibody secretion and cloned by limiting dilution. We obtained 32 stable clones secreting anti-influenza B HA human IgG, although most of these clones were obtained from one volunteer (SeaV-29) who had a robust immune response. We conclude that SPYMEG is a good fusion partner cell line, although cloning by limiting dilution may lead to significant loss of hybridomas.